The discourse of the crisis of the education: review to the model of competencies from the epistemology of education - de Proença-Lopes, Leandro; de Assis Zaremba, Fellipe (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article aims to analyze the discourse of crisis in education that permeates our contemporary society. It is observed from the fact that education did not carry out immediately its proposed principles for the education reform, this reform looked for promoting the admission called competences model. We are trying to check how the competences model has had an impact on the manner of a discourse of the crisis which is not given an educational task. To do this, we have developed an analysis of the educational reforms that were developed in the 1990s, we attempt to understand the context from a sociological perspective, and the schools were under pressure in order to prepare adequately the new capital requirements. To carry out the proposal, we believe that the concept of world’s disenchantment is useful to understand the attraction of the consumption fetishism, in relation with the disenchantment of the education. We concluded that it is predominant a logical set of instruments for education and adaptation, and that this was done to the extent that the intentions of the reform have been translated into public policies with the competences model. There is an intense process of mediation between the crisis of the education and not appropriation in the school space of the pedagogies of the competences, since this drives to the incapability to understand the epistemological tasks of the education, putting expectations in this one that are not of its competences, causing this way a speech of the crisis that reveals an attitude of alienation opposite to the widest problems of the society.